Análisis de costos de calidad en el proceso operativo de una empresa litográfica basado en el método PEF (2021)
In the current context, companies need to control the costs derived from their processes in order to generate competitive advantages in terms of productivity. The objective of this work is to study the quality costs in the operating process of a lithographic company located in the city of Bogotá. The PEF model was used to identify and quantify the costs associated with the process, the data was collected through observation, semi-structured interviews with the company's collaborators and internal document review. The information was analyzed using quality tools and techniques. From the study it is observed that the costs for internal and external failures are higher than the costs of prevention and evaluation, which implies an opportunity for improvement for the company under study. It is concluded that quality cost analysis facilitates decision-making in relation to cost reduction and improvement in organizational profitability.